Analysis of Red Onion Farming Income in Kayen Hill, Kedungjati Village, Kabuh District - Sadam Alif Abu Husaini; Yessita Puspaningrum; Siti Aminatus Zuhria (AGARICUS: Advances Agriculture Science & Farming, 2026)
This study aims to analyze production costs, revenue, and income of shallot farming in Kedungjati Village. The research method used is a quantitative descriptive method with a census sampling technique involving 30 shallot farmers. The data used in this study consist of primary data obtained through direct interviews using questionnaires, and secondary data obtained from related institutions. This study aims to analyze shallot farming in Kedungjati Village, covering production costs, revenue, income, and financial feasibility. The results indicate that the total production cost incurred by farmers per planting season—comprising fixed and variable costs—averaged Rp24,862,000, with variable costs (specifically seeds and labor) constituting the largest share of the cost structure. Farming revenue was derived from an average production of 1,800 kg sold at Rp20,000/kg, resulting in total revenue of Rp36,000,000 per planting season. Farming income—calculated as the difference between revenue and total production costs—amounted to Rp11,138,000 per planting season. The financial feasibility analysis yielded an R/C ratio of 1.45 (>1), indicating that the shallot farming operation is viable for development; as it generates revenue exceeding the costs incurred, the business is considered to provide added value and holds good prospects for continuation.